2006
DOI: 10.1128/jcm.01591-05
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Clinical Application of Electronic-Nose Technology to Early Detection ofMycobacterium tuberculosisin Culture and Sputum

Abstract: Ziehl-Neelsen (ZN) staining for the diagnosis of tuberculosis (TB) is time-consuming and operator dependent and lacks sensitivity. A new method is urgently needed. We investigated the potential of an electronic nose (EN) (gas sensor array) comprising 14 conducting polymers to detect different Mycobacterium spp. and Pseudomonas aeruginosa in the headspaces of cultures, spiked sputa, and sputum samples from 330 cultureproven and human immunodeficiency virus-tested TB and non-TB patients. The data were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 19 publications
1
99
0
1
Order By: Relevance
“…First of all, our in vivo findings extend the in vitro data of a number of research groups (43)(44)(45). These studies showed that A. fumigatus can be discriminated in vitro from multiple other microorganisms by an analysis of the metabolites they produce.…”
Section: Discussionsupporting
confidence: 57%
“…First of all, our in vivo findings extend the in vitro data of a number of research groups (43)(44)(45). These studies showed that A. fumigatus can be discriminated in vitro from multiple other microorganisms by an analysis of the metabolites they produce.…”
Section: Discussionsupporting
confidence: 57%
“…In more recent years, an increasing number of studies have focused on the application of sensor array-based devices (e-noses) to obtain volatile smell prints in order to discriminate between TB patients and noninfected controls (66)(67)(68)). An earlier study used electroconductive sensor-based e-nose technology for demonstrating the discrimination of M. tuberculosis from other bacterial species in sputum samples (66).…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…Interestingly, asthmatics can also be discriminated from healthy controls and COPD patients (cross-validated accuracy 80-100%) [163,164,174]. In addition, eNoses are an attractive screening method for infectious diseases [175,176]. It is important to notice that all these data are based on cross-validation procedures in so-called 'training sets'.…”
Section: Electronic Nose: Exhaled Molecular Profilesmentioning
confidence: 99%